Vitamin D Status and Its Relation to Inflammatory Markers in Patients with Mild to Moderate Ulcerative Colitis - Amrollah Sharifi; Saharnaz Nedjat; Homayoon Vahedi; Gholamreza Veghari; Mohammad Javad Hosseinzadeh-Attar (Middle East Journal of Digestive Diseases, 2018)
BACKGROUND Inflammatory bowel disease (IBD), Crohn’s disease (CD), and Ulcerative colitis (UC) are autoimmune inflammatory diseases of the alimentary tract, which seems to be caused by the interaction of environmental and genetic factors as well as diet and nutritional factors such as vitamin D. The aim of this study was to assess the vitamin D status and its associations with erythrocyte sedimentation rate (ESR), and high-sensitivity C-reactive protein (hs-CRP) as inflammatory markers in patients with UC.